(untitled) (Bangladesh Journal of Botany, 2019)
An experiment was conducted to study the population dynamics of rice earhead bug and to evaluate the efficacy of newer insecticide combinations and sole insecticide along with untreated control. The rice earhead bug population was first recorded on 36th standard week as 1 nos./10 sweep nets and peak population (17 nos./10 sweep nets) was observed during 44th standard week. The correlation analysis revealed that rice earhead bug showed significant negative correlation with rainfall while the remaining weather parameters like average relative humidity and average temperature were found negative and non-significantly correlated. The overall data of efficacy revealed that all insecticidal treatments were significantly superior over untreated control. However, the plots treated with fipronil 5% + buprofezin 20% SC recorded the lowest number of rice earhead bug population (2.10 and 3.51 nos./5 sweep nets) after first and second insecticidal sprays, respectively, followed by indoxacarb 10% + thiamethoxam 10% WG (2.47 and 4.25 nos./5 sweep nets, respectively). Whereas, application of thiamethoxam 25% WG and buprofezin 25% singly SC were recorded as third and fourth best treatments, respectively.